The Impact of Natives' Attitudes Towards Immigrants on Their Integration in the Host Country - Pia Schilling; Steven Stillman (Center for Economic Studies and ifo Institute (CESifo), 2021)
Exploiting the random allocation of asylum seekers to different locations in Germany, we study the impact of right-wing voting on refugees' integration. We find that in municipalities with more voting for the right-wing AfD, refugees have worse economic and social integration. These impacts are largest for groups targeted by AfD campaigns and refugees are also more likely to suffer from harassment and right-wing attacks in areas with greater AfD support. Positive interactions with locals are also less likely in these areas.
Keywords: J15; J61; Z13; 330; immigrants' integration; refugees; hostile attitudes; voting behaviour